Formation mechanism of coarse grained zone in annealed high Nb–TiAl–xB ingots. Issue 2 (22nd January 2016) - Zhang, Z. Y.; Xu, X. J.; Liang, Y. F.; Zhang, L. Q.; Lin, J. P.
Abstract : High Nb–TiAl ingots with various boron levels (0, 0.2, 0.5, 0.7 and 1.0 at-%) were investigated using annealing in a single α phase field for various lengths of time, and a coarse grained zone (CGZ) was observed when the boron content was greater than 0.5 at-%. Scanning electron microscopy and transmission electron microscopy were used to study microstructural evolution and boride transformation. Experimental results show that the width of CGZ is closely related with the boron addition and the cooling rate. The formation mechanism is discussed for various nucleation behaviors of boride at the ingot scale during solidification caused by the temperature induced supercooling and the boron induced compositional supercooling, which lead to dissimilar pinning effects of borides at high temperature.